A review on nanotechnology and its application in modern veterinary science - Kalkidan Mamo Woldeamanuel; Fufa Abunna Kurra; Yonas Tolosa Roba (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
The term nanotechnology refers to material processing on the atomic or molecular scale, especially for the construction of microscopic level devices with the ability to calculate, function, and organize. The microscopic level typically refers to the size range of 1-100 nm. We opt to review the application of nanotechnology in veterinary medicine for this specific article and highlight their functions in animal health and production improvement. Nanotechnology plays a key role in veterinary medicine and other areas of animal production and also plays a significant role in the treatment of diseases through the development of a system for the delivery of smart medicines. Nanotechnology has revolutionized virtually all veterinary medicine and animal science disciplines these days by offering new, small-scale devices and materials that are beneficial to living organisms. Nanoparticles used for disease detection, treatment, delivery of medications, animal breeding, and reproduction include quantum dots, magnetic nanoparticles, nanopores, polymeric nanoparticles, nanoshells, fullerenes, liposomes, and dendrimers. While nanotechnology is regarded as one of the foremost technologies already applied in diverse subjects, its application in veterinary science is still in its infancy stages when compared to other sister disciplines.